2018
DOI: 10.1111/1556-4029.13870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Swabs for Sampling Inorganic Gunshot Residue from Gunshot Wounds: Applicability and Reliability for the Determination of Firing Distance

Abstract: This study concentrates on samples of bare pork skin, with and without bristles, and dried bovine ribs shot with a semi-automatic pistol to find the best methodology and sampling surface in the search for inorganic gunshot residues (IGSR). Four quadrants of known surface areas were sampled at different distances from the bullet's hole with different swabs: tapes in graphite, Leukosilk® white tape, 3M® transparent tape, and a cotton swab to assess the technique able to collect the highest amounts of IGSR with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…in combination with a gunshot residue (GSR) analysis still appears to be the most productive approach for reliable differentiation between certain distances [11]. Particularly, the detection, quantification, and correlation of GSR with the shooting distance has been (with a focus on staining, e.g., [27]) and still is a promising field of research, including GSR detection via micro-CT [28] and the analysis of inorganic GSR [29] by emission spectrometry and mass spectroscopy, which, however, require advanced lab equipment. Hlavaty et al performed a microscopic, histological analysis of the tissue surrounding the bullet entry site to estimate the shooting distance but also concluded that this approach is not suitable for forensic routine analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…in combination with a gunshot residue (GSR) analysis still appears to be the most productive approach for reliable differentiation between certain distances [11]. Particularly, the detection, quantification, and correlation of GSR with the shooting distance has been (with a focus on staining, e.g., [27]) and still is a promising field of research, including GSR detection via micro-CT [28] and the analysis of inorganic GSR [29] by emission spectrometry and mass spectroscopy, which, however, require advanced lab equipment. Hlavaty et al performed a microscopic, histological analysis of the tissue surrounding the bullet entry site to estimate the shooting distance but also concluded that this approach is not suitable for forensic routine analysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the author network analysis, Amadasi was found to be the most prolific in co-authorship, and their last paper on gunshot residue was published in 2016. Using the search engine ResearchGate, another paper on gunshot residue was published in 2018 by Amadasi et al [34]. This discrepancy arose because ResearchGate reported the initial publication date as July 2018 and the Journal of Forensic Science where the article was published did so in 2019, and as such, the paper was not included within the Scopus search results.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 104 ], an investigation was conducted to compare different swabbing techniques and sampling areas, this to determine for shooting distance estimation the best sampling device and optimal sampling area around a gunshot wound. Inductively coupled plasma optical emission spectrometry and inductively coupled plasma mass spectrometry were used as quantification techniques.…”
Section: Shooting Distance Estimation and Bullet Hole Characterizationmentioning
confidence: 99%